The Risks of Using Homework in Middle Grades Math Classes - Hem, Alaina C. (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
The assigning of homework is a widely used practice in education. However, requiring it comes with several risks. First, many students have very different levels of parent involvement at home, meaning that some are at a disadvantage in terms of completing homework. Similarly, differences in resources at home affect students’ abilities to complete their homework. Language barriers and disabilities are also factors that can cause difficulties for students when they are at home and beyond the help of the teacher. In addition, homework can be very stressful for all parties involved. Before assigning homework, teachers should carefully consider the diverse needs, advantages, and disadvantages that their students have. They should understand their purposes for giving homework and decide if those purposes could be better served by using in-class activities.